A dual‐output single‐input non‐isolated DC‐DC converter with reduced semiconductors stress. (25th September 2022) - Radmanesh, Hamid; Jashnani, Hamidreza; Pourjafar, Saeed; Maalandish, Mohammad
Abstract: This work proposes a novel topology of two‐output high voltage rate DC‐DC converter based on coupled inductor and voltage multiplier cells (VMCs) techniques for renewable energy usages like photovoltaic (PV) systems. The proposed structure has two independent output ports with two voltage gains ( M 1 and M 2 ). Low voltage stress across the power switch and diodes, common ground between input and output ports, high efficiency, and reduced number of elements are the advantages of the suggested converter. The used diodes are switched at zero current switching (ZCS) and zero voltage switching (ZVS) conditions, which reduce the losses of diodes and subsequently increase the power efficiency. Due to the usage of the coupled inductor, there is no need to a high value of the power switch's duty cycle. Therefore, a low conduction loss and higher efficiency can be obtained. On the other hand, because of the reduced voltage stresses, low rated semiconductors can be used for operation of the presented converter, which decrease the cost and the volume. To demonstrate the performance and effectiveness of the proposed topology, operation principles, steady‐state and efficiency analysis, and also the comparison assessment are provided. Finally, a 200 W experimental development with 50 kHz operation frequency, 20 V input voltage, and 200 and 100 V loads voltages has been implemented in the lab to prove the mathematical surveys. Abstract : This work proposes a novel topology of two‐output high voltage rate DC‐DC converter based on coupled inductor and voltage multiplier cells (VMCs) techniques for renewable energy usages like photovoltaic (PV) systems. The proposed structure has two independent output ports with two voltage gains.